2003
DOI: 10.1177/009286150303700410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wyeth Medical Communications Written Responses and the Impact on Prescribing

Abstract: Objective: Wyeth's Global Medical Communications Department provides written standard responses to unsolicited requests for medical information related to Wyeth Products. A survey was conducted to evaluate the satisfaction of healthcare professionals with the written information provided and to assess the impact of satisfaction with the information on prescribing behavior. Methods: A business reply card containing seven qualitative questions with all standard response letters was mailed from September 1, 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…2 In fact, several studies have demonstrated that, in general, HCPs are satisfied with the information they received from industry-based MI departments (Pfizer Inc, unpublished data). 3 -6 Given the extensive and high-quality information that MI departments from pharmaceutical companies have, why is this resource not used more frequently among HCPs? What are the factors that determine utilization of a medical information resource?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In fact, several studies have demonstrated that, in general, HCPs are satisfied with the information they received from industry-based MI departments (Pfizer Inc, unpublished data). 3 -6 Given the extensive and high-quality information that MI departments from pharmaceutical companies have, why is this resource not used more frequently among HCPs? What are the factors that determine utilization of a medical information resource?…”
Section: Introductionmentioning
confidence: 99%
“…There was an interesting study published in 2003 by Santhouse and Albano 3 that evaluated the impact on prescribing after receipt of medical information from an industry-based MI department. In this study, more than 800 HCPs (including over 400 physicians) responded to a survey that included questions related to the quality of information and the impact of the information on their prescribing decisions.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, many companies have conducted benchmarking surveys to solicit unbiased and relevant feedback on their overall MI services from customers. 1 -8 These survey results provided valuable information on the needs of the customers and may help companies assess their internal operational processes and shape strategic directions. Though there have been multiple surveys conducted to assess areas of improvement across several companies, specific surveys to gain insights on the utility of MI services across the pharmaceutical industry, as well as understanding if the information provided the evidence necessary to prescribe with confidence have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…They provide external validation of quality and identify areas for improvement. Surveys can be used as a tool for evaluating the services of Medical Communications Departments (1)(2)(3)(4)(5). When Medical Communications Departments utilize surveys, they are typically distributed to requesters of medical information such as health care providers and sales representatives.…”
Section: Introductionmentioning
confidence: 99%
“…When Medical Communications Departments utilize surveys, they are typically distributed to requesters of medical information such as health care providers and sales representatives. Studies have been published describing experiences and findings of customer surveys (1)(2)(3)(4)(5). The authors of these studies identified areas for improvement of departmental deliverables based on their findings.…”
Section: Introductionmentioning
confidence: 99%